2015
DOI: 10.1097/ta.0000000000000492
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the implementation of acute care surgery

Abstract: BACKGROUND To date, no studies have reported nationwide adoption of Acute Care Surgery (ACS) or identified structural and/or process variations for the care of emergency general surgery (EGS) patients within such models. METHODS We surveyed surgeons responsible for EGS coverage at University HealthSystems Consortium hospitals using an 8-page postal/email questionnaire querying respondents on hospital and EGS structure/process measures. Survey responses were analyzed using descriptive statistics, univariate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…This is likely due to the fact that hospitals adopting ACS are more likely to take on that role across many diagnoses (e.g. urban, larger inpatient bed capacity, higher trauma center verification) (29, 30). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely due to the fact that hospitals adopting ACS are more likely to take on that role across many diagnoses (e.g. urban, larger inpatient bed capacity, higher trauma center verification) (29, 30). …”
Section: Discussionmentioning
confidence: 99%
“…The survey was implemented using a hybrid postal and email methodology targeting a single senior surgeon at each hospital who would be able to respond to queries regarding the structures and processes for EGS care at their hospital as described previously (30). The survey was implemented from June 2013 to November 2013.…”
Section: Methodsmentioning
confidence: 99%
“…Adipose tissues, both WAT and BAT, are highly affected during obesity. These alterations include adipocyte hyperplasia and hypertrophy [100], endoplasmic reticulum stress [101], oxidative stress [102], fibrosis [100] and mitochondrial dysfunction [103], among others. Obesity is associated with severe disorders such as cardiovascular disease, dyslipidemia, T2D or even some forms of cancer.…”
Section: Activating Bat To Treat Obesitymentioning
confidence: 99%
“…The barriers to achieving high-quality, safe, and effective emergency general surgical care across health systems are manifold and multifactorial. Within the United States of America previous indications [1] had suggested that specific national quality targets for EGS were being realised. This work had advocated the application of a quality improvement approach, founded upon the Donabedian Model, and introduction of accepted guidelines to EGS care.…”
Section: The Pursuit Of Qualitymentioning
confidence: 99%